Reading Learning Management Based on Flash Card Games in Improving the Quality of Students' Psychomotor Learning at PAUD Ar-Ridho - Teti Ratnawulan; Ahmad Rifandi; Ani Nuraeni; Listia Rismayanti; Sisca Rachmawati; Yudah Ardiansyah; Imam Asrofi (Universitas Muhammadiyah Enrekang, 2025)
This study aims to describe the implementation of a reading learning management based on flash card games in improving the quality of psychomotor learning among students at PAUD AR-RIDHO. The background of this research is based on the importance of early reading skills in young children, which involve not only cognitive aspects but also psychomotor aspects, such as hand-eye coordination and fine motor skills. Flash cards, as visual and interactive learning media, are considered effective in attracting children's attention and supporting psychomotor skill development through fun and meaningful activities. This research employs two methods are qualitative and descriptive quantitative approaches, with data collected through observation, interviews, and documentation. The subjects of the study were teachers and students of Group B at PAUD AR-RIDHO. The results showed that systematic and well-planned use of flash cards in reading activities increased students’ active engagement, strengthened their visual memory, and trained fine motor coordination through activities such as matching, lifting, and pronouncing letters or words on the cards. Moreover, flash card-based learning created an enjoyable and stress-free learning atmosphere, positively impacting the overall quality of psychomotor learning. Therefore, this strategy can be considered an effective alternative for teaching reading at the early childhood education level. The study recommends that teachers receive training in designing and developing varied flash card media tailored to the characteristics of young learners.